A randomized sublinear time parallel GCD algorithm for the EREW PRAM - Sorenson, Jonathan P. (Information processing letters, 2010)
We present a randomized parallel algorithm that computes the greatest common divisor of two integers of n bits in length with probability 1 − o ( 1 ) that takes O ( n log log n / log n ) time using O ( n 6 + ϵ ) processors for any ϵ > 0 on the EREW PRAM parallel model of computation. The algorithm either gives a correct answer or reports failure. We believe this to be the first randomized sublinear time algorithm on the EREW PRAM for this problem.